A highly selective colorimetric and fluorescent dual‐modal probe for the rapid determination of fluoride anions. (16th March 2017) - Li, Changsuo; Tang, Chengcheng; Xing, Liting; Sun, Bin; Cheng, Shiyu; Liao, Qiang; Zhu, Baocun
Abstract: In this work, 4‐( p ‐hydroxybenzylidenehydrazino)‐ N ‐butyl‐1, 8‐naphthalimide (1 ) has been designed and synthesized as a colorimetric and fluorescent dual‐modal probe for F − . Compound1 immediately detected inorganic fluoride salts using U V / v is absorption and fluorescence spectroscopy methods, and served as a 'naked‐eye' indicator for F − with high selectivity and sensitivity. Both the absorption and fluorescence spectra show excellent linearity with the concentration of F − . Real‐life applications demonstrated that our proposed analytical system provided a satisfactory method for the determination of F − . In addition, the reaction mechanism of deprotonation was confirmed by 1 H NMR.